Study on the formation and development of aromatic rice spikelets - Anh Thu Quang; Cong Thanh Vo (Vietnam Journal of Science, Technology and Engineering, 2017)
In order to detect some of the determinants of rice flavor, an experiment was carried out that studied panicle primordia at the initial panicles of three aromatic varieties: Nang Thom Cho Dao mutation (NTCDm), Thom Bay Nui (TBN), and Jasmine-85, and IR28 was used as the control variety (non-aroma). The samples were dyed from the primordium stage to the ripe-pollen stage. Results showed that there were two key differences between the aromatic rices and the control. The first point of difference was at the primordium stage, and the second was after, as a consideration of the number of bivalents (pairs of homologous chromosomes). As for the three aromatic rice varieties, there appeared a lobe division at the branch primordium; at the diplotene stage of meiosis, and seven to eight stained bivalents appeared while the control had no lobe division and the number of stained bivalents achieved 11 to 12.